Cancer Epidemiology Research In Indonesia Based On Riskesdas - HEALTH, NATIONAL INSTITUTE (Indonesian Journal of Cancer, 2010)
https://www.scribd.com/doc/43600150/Cancer-Epidemiology-Research-In-Indonesia-Based-On-Riskesdas